Optimization of Lip Cream Formula with Teak Leaf Extract (Tectona grandis L.f.) and Carnauba Wax Base Using the Simplex Lattice Design Method - Anik Zahrotul Mungizah; Afi Sania Rosanti; Riza Dwiningrum; Mida Pratiwi (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Lip cream is a decorative cosmetic preparation that functions to beautify and moisturize the lips. However, most lip cream still use synthetic colorants that are toxic and cause irritation, such as Rhodamin B. Therefore, teak leaf extract (Tectona grandis L.f.), which contains anthocyanins, wa chosen as the base due to its physical properties that support the stability of the formulation. This study aimed to optimize the lip cream formula using a combination of teak leaf extract and carnauba wax, analyzed through the Simplex Lattice Design method. The study used an observational method involving various formulations with different concentrations of teak leaf extract and carnauba wax, followed by evaluation of physical properties, including organoleptic characteristics, ph, homogenity, protective ability, spreadability, and adhesion. The optimal formula was found at 5% teak leaf extract and 15% carnauba wax, with an average ph of 6, spreadability of 6,2 cm, and adhesion of 4,11 seconds. The preparation appeared homogeneous, stable, and effective in protecting the lips. The combination of teak leaf extract and carnauba wax can be formulated into a natural lip color cometic preparation that meets quality standards, maintains stability, and is safe for use.